Local Government Authority in Forest Protection in Tagafura Protected Forest Area, Tidore Islands City - Muhammad Julham (Sangia Publishing, 2020)
The research objective was to determine the authority of local governments in forest protection based on Law Number 32 of 2004 and Law Number 23 of 2014 concerning Regional Government and to see the implications of the transfer of personnel, facilities and infrastructure, and documents on the protection of the Tagafura Protected Forest Area. , Tidore Islands City. This research used interview and document study methods. The data collected were analyzed qualitatively and descriptively. The research was conducted at the Tidore Islands City Government, the North Maluku Provincial Forestry Service Office and the Kalaodi Urban Village Office. This study found that: (1) the authority of the government based on Law Number 32 of 2004 lies in the regency or city, while in Law Number 23/2014, this authority is transferred to the provincial government; (2) The transfer of personnel, transfer of facilities and infrastructure as well as documents on efforts to protect the Tagafura Protected Forest Area did not proceed properly.